Achievements and challenges of undergraduates in science, technology, engineering, and mathematics fields in the Ronald E. McNair Program - Farro, Samantha Anne, author; Canetto, Silvia S., advisor; MacPhee, David, advisor (Colorado State University. Libraries, 2009)
This dissertation is comprised of two studies and is about understanding the challenges, choices, aspirations, and perceptions of successful, underrepresented undergraduates in STEM fields. Study 1 compared self-perceptions of academic ability and academic performance of female and male undergraduate science and engineering students from underrepresented ethnic and socioeconomic groups, upon admission in (Time 1) and graduation from (Time 2) the McNair Mentorship Program. Female and male students were similar in regard to academic performance. However, at Time 1, women were significantly more likely than their male peers to describe themselves as academically weaker. Upon graduation from the McNair Program, women's perceptions of their academic skills were on par with those of men. Students with double minority status (i.e. by sex, ethnicity, generation in college, or income) had more negative self perceptions of academic skills, as well as lower performance on standardized tests. Overall, these findings suggest that one barrier for women in STEM education is lower confidence. However, over time female McNair students in STEM increased their self-perception of academic competence. This study's findings also indicate that multiple minority status may have a cumulative negative impact on academic self-perceptions and academic performance. Study 2 focused on the experiences of high-achieving, female undergraduates from disadvantaged backgrounds who are majoring in engineering, physical, or life science. Interviews about educational choices and career aspirations were collected in written form upon admission to (Time 1) and graduation from (Time 2) the McNair Mentorship Program. Students' timing of educational and career decisions, motivations, parental expectations and involvement in educational and career planning, career exploration, and career aspirations were qualitatively analyzed longitudinally and across disciplines. Insights about educational choices and career aspirations are shared and recommendations are given for future research to improve career counseling to support disadvantaged women in STEM fields.
Keywords: career development; education; McNair mentorship; Ronald E. McNair Program; science, technology, engineering, and mathematics; undergraduate; underrepresented students; women in STEM; women students; social psychology; women's studies; educational psychology